Associations between preference and participation in team sports: Physical activity promotion among adolescents - Frömel, Karel; Mitáš, Josef; Groffik, Dorota; Kudláček, Michal; Háp, Pavel (Frontiers in Public Health, 2022)
Background: The level of physical activity (PA) in adolescents is highly dependent on their PA preferences. PA preferences among adolescents are dominated by team PA, mostly team sports (TS). The aim of this study is to identify (a) the status and trends in the preferences of TS among Czech and Polish boys and girls in different educational and sports environments, and (b) the impact of the agreement between the preferred and simultaneously pursued TS on the structure of weekly PA and on the meeting of PA recommendations. Methods: The research was carried out between 2009 and 2022 in the Czech Republic and Poland and included 2939 boys and 4427 girls aged 15 to 19 years. Preferences and participation in TS were identified using a PA preference questionnaire and weekly PA using the International Physical Activity Questionnaire-Long Form. Trends in TS preferences were analyzed over seven two-year periods. The participants were divided into groups by agreement and disagreement between the preferred and pursued TS, and by agreement and disagreement between the preferences of TS and participation in organized TS. Results: Throughout the 14-year study period, boys in both countries preferred soccer, whereas girls favored volleyball. Agreement between preferences and participation in TS increased vigorous PA in Czech and Polish boys and girls. The agreement between the preferences for TS and participation in organized TS had the most significant effect on increasing vigorous PA in Czech and Polish boys and girls and on total PA in boys in both countries. Those who preferred and participated in TS were more likely to meet PA recommendations. Conclusions: Respecting the status and trends of TS preferences in supporting participation in TS increases adolescents’ PA and their achievement of PA recommendations. Increasing active participation in organized TS among boys and girls may support regular PA and help eliminate the negative effects of the pandemic on adolescents’ PA.